2015
DOI: 10.1158/1535-7163.mct-14-0614
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2A Inhibition with LB100 Enhances Radiation-Induced Mitotic Catastrophe and Tumor Growth Delay in Glioblastoma

Abstract: Protein Phosphatase 2A (PP2A) is a tumor suppressor whose function is lost in many cancers. An emerging, though counterintuitive, therapeutic approach is inhibition of PP2A to drive damaged cells through the cell cycle, sensitizing them to radiation therapy. We investigated the effects of PP2A inhibition on U251 glioblastoma cells following radiation treatment in vitro and in a xenograft mouse model in vivo. Radiation therapy alone augmented PP2A activity, though this was significantly attenuated with combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
(29 reference statements)
3
43
0
Order By: Relevance
“…It has been conclusively shown that PP2A inhibition in tumor cells leads to a downregulation of the DNA-damage response [15,18,34] and the abrogation of cell cycle checkpoints to achieve preferential killing [15,34,35]. Consistent with those findings, we have shown that LB100 inhibited proliferation and induced a G2/M arrest in MEC cells.…”
Section: Discussionsupporting
confidence: 90%
“…It has been conclusively shown that PP2A inhibition in tumor cells leads to a downregulation of the DNA-damage response [15,18,34] and the abrogation of cell cycle checkpoints to achieve preferential killing [15,34,35]. Consistent with those findings, we have shown that LB100 inhibited proliferation and induced a G2/M arrest in MEC cells.…”
Section: Discussionsupporting
confidence: 90%
“…Cells progress to mitosis, but spindle formation is disordered and mitotic catastrophe occurs [84, 95, 96, 98, 99]. Disrupted cell cycle progression was further evident in cell cycle spread analyses, where treatment with a DNA damage inducer led to predominant S-phase arrest (more cells in G1/S), but when combined with PP2A inhibition by LB100, cells progress through S-phase and accumulated in G2/M due to disordered mitosis [84, 95, 96, 98-100]. PLK1 inhibition of TCTP, a protein that stabilizes microtubules and has anti-apoptotic functions, may contribute to abnormal mitotic figures and mitotic catastrophe [84, 96].…”
Section: Pp2a Inhibitionmentioning
confidence: 99%
“…In addition to irregular cell cycle regulation, a few studies reported persistence of DNA damage with LB100 treatment, which was indicated by presence of γ-H2AX foci [96, 98-100]; likewise, LB100 inhibited Rad51 foci formation as part of DDR [97]. This suggests that homologous recombination (HR) repair may also be impaired by LB100, which is unsurprising given PP2A’s additional roles in regulating damage repair.…”
Section: Pp2a Inhibitionmentioning
confidence: 99%
“…As with fostriecin, the lead compound, LB-100, and its lipid-soluble homolog, LB-102, inhibited proliferation of cell lines from a variety of human solid tumors at low micromolar concentrations (9). More strikingly, both compounds potentiated the activity, without significantly increasing the toxicity, of cisplatin, doxorubicin, and temozolomide against xenografts of pancreatic (10) and hepatocellular carcinoma (11), fibrosarcoma (12), pheochromocytoma (13), neuroblastoma (14), and glioblastoma (14) and of focal X-ray against pancreatic (15), nasopharyngeal (16), and glioblastoma xenografts (17). In addition, LB-100 reversed resistance to cisplatin in ovarian carcinoma (18) and medulloblastoma (19) xenografts.…”
Section: Introductionmentioning
confidence: 98%
“…Wei and colleagues (15) demonstrated that inhibition of PP2A by LB-100 sensitized human pancreatic cell lines in culture and as xenografts to radiation by interfering with DNA repair. Moreover, Gordon and colleagues (17) showed that LB-100 enhanced radiation inhibition of glioblastoma xenografts by interfering with mitotic exit, leading to increase mitotic catastrophe. Additional support for the potential value of PP2A inhibition for enhancing cytotoxic therapy was provided by Chang and colleagues (18), who demonstrated that LB-100 sensitized human ovarian cancer xenografts to cisplatin, at least in part by altering cell-cycle checkpoint regulation.…”
Section: Introductionmentioning
confidence: 99%